Pseudoaneurysm due to femoral artery puncture: a review - González-Martínez, Itaty C.; Granados-Romero, Juan José; Montalvo-Hernández, Jorge; Vázquez-González, Juan C.; Palacios-Rodríguez, Patricia M.; Mendizabal-Velazquez, Alondra; Abundez-Pliego, Ana L.; Valderrama-Treviño, Alan I.; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2023)
The femoral artery is the most used percutaneous access site for different endovascular therapeutic options, this being an excellent anatomical site to achieve adequate compression after its puncture, which frequently makes it the site with the highest incidence of complications associated with posterior to arterial puncture. The most frequent complications related to arterial puncture are: hematoma, pseudoaneurysm, retroperitoneal hematoma, and arterial occlusion. The pseudoaneurysm is defined as the interruption in the wall of the artery, product of the lesion of the wall, which causes blood leakage towards the surrounding tissues, remaining contained in a fibrin sac, therefore, the importance of an adequate diagnosis and treatment lies above all in the high risk of rupture or thromboembolism.